Recent and emerging applications of Graphene-based metamaterials in electromagnetics - Meisam Esfandiari; Ali Lalbakhsh; Paria Nasiri Shehni; Saughar Jarchi; Mohsen Ghaffari-Miab; Hamideh Noori Mahtaj; Sam Reisenfeld; Mohammad Alibakhshikenari; Slawomir Koziel; Stanislaw Szczepanski (Materials & Design, 2022)
Surface Plasmon Polaritons (SPPs) operating in mid-infrared up to terahertz (THz) frequencies have been traditionally manufactured on expensive metals such as gold, silver, etc. However, such metals have poor surface confinement that limits the optical applications of SPPs. The invention of graphene is a breakthrough in plasmon-based devices in terms of design, fabrication and applications, thanks to its plasmonic wave distribution, low-cost prototyping and its inherent reconfigurability. In addition, recent advancements in plasmon-based metamaterials and metasurfaces led to the elimination of the past constraints on regular optical devices, opening a new door in THz devices and applications. This paper provides an operational perspective of the advanced graphene-based electromagnetic devices, with a focus on graphene enabled antennas, absorbers and sensors, analyzing the strengths and limitations of various design methodologies.